2020
DOI: 10.3390/fluids5010013
|View full text |Cite
|
Sign up to set email alerts
|

Density, Viscosity and Free Energy of Activation for Viscous Flow of Monoethanol Amine (1) + H2O (2) + CO2 (3) Mixtures

Abstract: Densities and viscosities of aqueous monoethanol amine (MEA) and CO2-loaded aqueous MEA are highly relevant in engineering calculations to perform process design and simulations. Density and viscosity of the aqueous MEA were measured in the temperature range of 293.15 K to 363.15 K with MEA mass fractions ranging from 0.3 to 1.0. Densities of the aqueous MEA were fitted for a density correlation. Eyring’s viscosity model based on absolute rate theory was adopted to determine the excess free energy of activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Consequently, the maximum temperature of the density measurements was limited to 323.15 K for some CO2-loaded aqueous amine mixtures to reduce the experimental errors. The uncertainties in density and viscosity measurements are reported in references [23,24]. The study reveals that properly trained feedforward backpropagation ANN models are capable of predicting physical properties of alkanolamine + H 2 O + CO 2 mixtures with good accuracy and models are appropriate for engineering applications of designing process equipment and performing mathematical modelling and simulations of absorption and desorption systems.…”
Section: Viscosity From Ann Based Models and Empirical Correlationsmentioning
confidence: 97%
See 4 more Smart Citations
“…Consequently, the maximum temperature of the density measurements was limited to 323.15 K for some CO2-loaded aqueous amine mixtures to reduce the experimental errors. The uncertainties in density and viscosity measurements are reported in references [23,24]. The study reveals that properly trained feedforward backpropagation ANN models are capable of predicting physical properties of alkanolamine + H 2 O + CO 2 mixtures with good accuracy and models are appropriate for engineering applications of designing process equipment and performing mathematical modelling and simulations of absorption and desorption systems.…”
Section: Viscosity From Ann Based Models and Empirical Correlationsmentioning
confidence: 97%
“…Figure 1 illustrates a schematic of neurons in an ANN consisting of one hidden layer with a single output. The measured data by the authors to perform this study can be found in the sources [23,24]. Table 3 In the developed ANN models, the mole fractions of components and the temperature are considered as the inputs for the network.…”
Section: Ann Trainingmentioning
confidence: 99%
See 3 more Smart Citations